Vat Photopolymerization Additive Manufacturing of Functionally Graded Materials: A Review - Nohut, Serkan; Schwentenwein, Martin (Journal of Manufacturing and Materials Processing, 2022)
Functionally Graded Materials (FGMs) offer discrete or continuously changing properties/compositions over the volume of the parts. The widespread application of FGMs was not rapid enough in the past due to limitations of the manufacturing methods. Significant developments in manufacturing technologies especially in Additive Manufacturing (AM) enable us nowadays to manufacture materials with specified changes over the volume/surface of components. The use of AM methods for the manufacturing of FGMs may allow us to compensate for some drawbacks of conventional methods and to produce complex and near-net-shaped structures with better control of gradients in a cost-efficient way. Vat Photopolymerization (VP), a type of AM method that works according to the principle of curing liquid photopolymer resin layer-by-layer, has gained in recent years high importance due to its advantages such as low cost, high surface quality control, no need to support structures, no limitation in the material. This article reviews the state-of-art and future potential of using VP methods for FGM manufacturing. It was concluded that improvements in printer hardware setup and software, design aspects and printing methodologies will accelerate the use of VP methods for FGMs manufacturing.